Persepsi Mahasiswa Terhadap Penggunaan Literasi Digital Di Fakultas Tarbiyah Unsiq Jawa Tengah Di Wonosobo - Niken Ayu Safitri; Rifqi Muntaqo; Ali Imron (Jurnal Kajian dan Penelitian Umum, 2024)
The majority of students rely on Digital Literacy as their primary learning tool. Additionally, the student's source for receiving lecture material has been included, and lecturers deliver lectures to students in accordance with the existing lecture contract. The objective of this qualitative field study is to describe and comprehend how students at the UNSIQ Central Java Tarbiyah Faculty in Wonosobo perceive the use of digital literacy. Sixth-year PAI students served as the study's subjects. Interviews, online questionnaires, and documentation are used in the method of data collection. Qualitative descriptive analysis is used in data analysis. The study found that PAI sixth-semester students have positive perceptions of the use of digital literacy. These students' perceptions of the use of digital literacy are categorized as positive and agreeable; they describe the ease, pleasure, and comfort they experience when using digital literacy both in lectures and in everyday life. While many sixth-semester PAI students use the internet as a source for academic assignments without paying attention to the source, their ability to manage information remains in the medium category. Also, this examination shows that most of understudies have fundamental web abilities.